Assessing the quality of mangrove ecosystem as breeding sites organisms in the coastal area - Susi Mulia Ulva; Djufri Djufri; Supriatno Supriatno; Safrida Safrida; Ismul Huda (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Mangrove ecosystem is an ecosystem that supports people's lives and the biota that live in it. Globally, mangrove ecosystems are recognized as productive ecosystems in coastal areas. Mangrove wetlands have an important function of protecting coastal ecology, buffering salinity, breeding grounds for organisms and transporting nutrients. Research on the assessment of the quality of mangrove ecosystems in Syiah Kuala District, Banda Aceh City was carried out with the aim of studying the presence of mangrove species, plankton species, hydrological factors of mangrove ecosystems and analyzing the quality of mangrove ecosystems as breeding grounds for organisms based on hydrological factor values. The method used in this study was the line transect method and the research technique was carried out by means of purposive sampling. Data analysis was calculated using the Shanon-Wiener Species Diversity Index () and PCA (Principal Component Analysis) analysis. Identification results showed a low mangrove species diversity index with a value of = 1.924, a plankton species diversity index of = 2.614 belonging to moderate community stability, a hydrological index covering temperatures ranging from 28.2 to 29.8 C, pH 7.1 -7.4, DO 2.9-4.1 mg/L, salinity 27-20.9 /, brightness 30-68.5 Cd, depth 88.5-105 cm. Water quality parameters are in good condition. PCA analysis showed a correlation between the distribution of mangrove species and parameters of salinity, pH, DO, temperature, depth and brightness.Keywords:MangrovesBreeding SiteHydrologyPlanktonCoastal Area